La démocratisation de l’accès aux images satellite : un enjeu de citoyenneté ? - Gwenaël Régnier (L'Espace Politique)
In recent years, the massive dissemination of satellite images to document disasters (such as devastating fires in Canada, earthquake in Turkey) or conflicts (like the war in Ukraine) through various medias, shows a turning point in the use of a source of information long restricted to intelligence or a specific professional use because of its strategic interest or its cost. Since the mid-2000s, the “digital revolution” and with it Google Earth and then open data have changed the situation. This article seeks to show how this democratization of access to satellite images can contribute to a better awareness of environmental issues but also to a form of citizen empowerment, understood here as the ability given to individuals to be able to better inform themselves in favour of greater transparency, in a world shaken by the climate emergency and growing spread of fake news. It defends the idea that the satellite image can be related to a "citizen-tool" and relies on action-research to propose a method aimed at promoting education in space imagery in secondary education, prior to an appropriation of the tool by the citizen. After recalling the main steps that led to the democratization of access to satellite images, it will focus on explaining how the satellite image is a citizen-tool that makes it possible to understand the today’s major societal issues and then it will show how an “education in spatial imagery” can be implemented in a practical way in the teaching of geography. While the pedagogical paths proposed in the light of action research tend to show that the satellite image makes it possible to favourably engage students in developing both geographical and transversal skills, the article calls for questioning the place of the satellite image in secondary education in France from a citizen perspective that extends the disciplinary framework on which it relies (here geography).